2016
DOI: 10.1007/s00418-015-1400-9
|View full text |Cite
|
Sign up to set email alerts
|

Actin, actin-binding proteins, and actin-related proteins in the nucleus

Abstract: Extensive research in the past decade has significantly broadened our view about the role actin plays in the life of the cell and added novel aspects to actin research. One of these new aspects is the discovery of the existence of nuclear actin which became evident only recently. Nuclear activities including transcriptional activation in the case of all three RNA polymerases, editing and nuclear export of mRNAs, and chromatin remodeling all depend on actin. It also became clear that there is a fine-tuned equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 196 publications
(226 reference statements)
2
86
0
2
Order By: Relevance
“…Accumulating data have revealed that actin also exists in the nucleus (Pederson & Aebi 2002;Bettinger et al 2004;Kristo et al 2016) and is required for transcription and other processes in the nucleus (Miralles & Visa 2006;Percipalle & Visa 2006;Falahzadeh et al 2015). Previous studies showed that actin interacts with Pol I, II and III and plays a key role in basal transcription Hu et al 2004;Philimonenko et al 2004;Ye et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data have revealed that actin also exists in the nucleus (Pederson & Aebi 2002;Bettinger et al 2004;Kristo et al 2016) and is required for transcription and other processes in the nucleus (Miralles & Visa 2006;Percipalle & Visa 2006;Falahzadeh et al 2015). Previous studies showed that actin interacts with Pol I, II and III and plays a key role in basal transcription Hu et al 2004;Philimonenko et al 2004;Ye et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since the existence of nuclear actin was confirmed, subsequent studies also established the presence of ABPs in the nucleus (12,14,15). The very first nuclear ABP was reported as early as 1987, henceforth, the rest of the ABP family in the nucleus has come to light comprising of proflilin, anillin, flightless I (Fli I), filamin α (FLNα), α-actinins, myosins, gelsolin and ezrin-radixin-moesin proteins (12,13,16,17). Although these ABPs are primarily in the cytoplasm, they can translocate into the nucleus under certain circumstances, for example, extracellular stimuli (stress), hormone stimulation and intracellular signaling (16).…”
Section: Actin and Actin-binding Proteins (Abps) In The Nucleusmentioning
confidence: 97%
“…Studies in the recent decades provide a plethora of evidence that has broadened our horizon on the functions of nuclear actin and nuclear ABPs in the eukaryotic cell life (12)(13)(14). Since the existence of nuclear actin was confirmed, subsequent studies also established the presence of ABPs in the nucleus (12,14,15).…”
Section: Actin and Actin-binding Proteins (Abps) In The Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural determinants are of crucial importance for nuclear organization. Current knowledge on nuclear actin is reviewed in "Actin, actin-binding proteins, and actin-related proteins in the nucleus" (Kristó et al 2016), whereas Harata and coworkers present data on the interaction of nuclear F-actin and β-catenin (Yamazaki et al 2016). Aspects of the growth of another structural entity, the nuclear lamina, were presented by Zhironkina et al (2016).…”
mentioning
confidence: 99%